ANALISIS VERTIKAL DAN HORIZONTAL TERHADAP LAPORAN KEUANGAN PT PERKEBUNAN NUSANTARA III (PESERO) MEDAN - Tinambunan, Anitha Paulina (UNIKA Santo Thomas, 2017)
This study aims to see the development of assets, profit / loss and observe financial ratios as projected financial performance of PT Perkebunan Nusantara III (PTPN III) Medan for the last 3 years ie the period of 2010 until 2012. From the results of vertical analysis known factors Causing the fluctuation of PTPN III financial ratios are: a) Liquidity increases due to the decrease in short-term liabilities; B) Solvency increases as a result of the increase in total debt; C) The creditability of accounts receivable collectability has improved; D) The profitability of a company decreases due to lower net income, increased assets and equity; E) Declining profitability is caused by the global economic crisis. While the results of comparison analysis are: 1) Current assets increased in 2011 and decreased in 2012 resulting from a reduction in cash, cash equivalent of third party receivables; 2) Fixed assets due to increased ownership of facilities / infrastructure and buildings; 3) Short-term debt increased in 2011 but decreased in 2012 due to decreased contractor debt, tax debt and bank debt; 4) Long-term debt increased due to increased deferred employee benefits and deferred tax liabilities; 5) Increased equity caused by increased issued and paid-up capital of the company; 6) Reduced net sales of palm oil, rubber and palm kernel and its derivatives due to falling selling prices; 7) Net income increased in 2011 but in 2012 is reduced and far from the planned company.